(untitled) (TAJ: Journal of Teachers Association, 2019)
Introduction: Tibia is a subcutaneous bone and is more prone to trauma. Different treatment modalities exist for fracture shaft of the tibia. Intramedullary nailing in the treatment of fractures of the long bones was technically developed and popularized by Küntscher in the 1940’s. Treatment of tibial fracture in adult is a challenge to orthopedic surgeons due to poor soft tissue coverage and blood supply. Materials and methods: This study was prospective and interventional. This study was carried out in the private hospitals in Rajshahi over a period of 3 years. Total 35 patients with tibial shaft fracture were studied. Inclusion criteria were displaced closed diaphyseal fracture shaft of the Tibia, open fracture with Gustillo 1, 2 and 3A attended within 24 hours. Exclusion criteria were patient’s age below 16 years, grossly lacerated fracture, undisplaced fracture, patient unwilling to operate. Thirty three cases were operated within one week only two cases operated at 2 months due to angulations following conservative treatment. Open fracture was fixed within 24-48 hours. Broad spectrum antibiotic injectable Moxifloxacin was used in most of the cases for 2 doses then oral, Injectable Meropenem was used for the open fracture. Those patients suffering from G-3A fracture wound were covered by Hemisoleal flap Two weeks after primary surgery and were uneventful. In most of the cases image intensification was not used only three cases needed image intensification in case the fractures in lower ¼ th of the shaft to see the end of the Nail. Results: Two patients developed postoperative superficial wound infection which was recovered by regular dressing. Only one patient needed post-operative cast support because the fracture was comminuted. All patients started Knee bending from first post-operative day. Full range of knee movement was found in all patients. All fracture united properly within 12 weeks to 22 weeks with mean of 17 weeks. No cases of implant failure detected during the study period. Conclusion: The results of the current study reveal that the reamed interlocking nail in treatment of tibial diaphyseal fracture is safe, easy, successful and preferable method may be recommended as a stable fixation with early return to daily activities. TAJ 2019; 32(1): 9-16